Upaya Pencegahan Pelanggaran HAM oleh Korporasi dalam Perspektif HAM dan Bisnis - Samanha, Rizki Atsari; Hayati, Tri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Violations of human rights by corporations occur due to technological advances that compel and the weakness of the system of laws and regulations as well as punishment for violators, resulting in acts of human rights violations both directly and indirectly. In order to analyze efforts to prevent human rights violations by corporations, human rights and business perspectives are needed and use normative research methods and present effective and appropriate prevention efforts. Thus, human rights violations committed by corporations are divided into 3 (three), namely forced migration of local residents, discrimination or closed access to justice and environmental damage. Therefore, the involvement of the state, corporations and society is needed in the implementation of corporate business entities to prevent and as an effort to mitigate human rights violations in the business sector.